Lucjan Rydel jako badacz i wydawca literatury dawnej – dzieje edycji „Jerozolimy wyzwolonej” Torquata Tassa w przekładzie Piotra Kochanowskiego (Kraków 1902–1903) - Kacprzak , Marta M. (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
The article discusses the research and editing work of Lucjan Rydel related to the Old Polish literature - the two-volume edition of Torquato Tasso’s Gerusalemme liberata, translated by Piotr Kochanowski as Goffred albo Jeruzalem wyzwolona, prepared by Rydel and published in Krakow in 1902-1903 by Polish Academy of Arts and Sciences in the series Biblioteka [96] Marta M. Kacprzak Pisarzów Polskich (Polish Writers’ Library). It is the result of Rydel’s research on the life and work of Piotr Kochanowski - Jan Kochanowski’s nephew, Renaissance poet, Polish translator of Ariosto and Tasso. In the Biblioteka Pisarzów Polskich it was planned to publish, in addition to Goffred, a 5-volume edition of Ariosto’s Orlando furioso translated by Piotr Kochanowski and a monograph on Kochanowski. Rydel’s materials for these books were lost during World War II, but they are known from the accounts of Józef Tretiak and Roman Pollak. Rydel’s edition of Goffred was critically reviewed by Adam Antoni Kryński, Ignacy Chrzanowski and Aleksander Brückner.